Medical Tourism and Its Role in Marketing Jordan Abroad - Alsarayreh, Mohammad Nayef; Al Nawaiseh, Kafa Hmoud Abdallah; Mahasneh, Mohammad Sultan Majed; Abu Rumman, Mohammed Abdul Razzaq (International Review of Management and Marketing, 2017)
Jordan is one of the most developed countries in the field of Medical Tourism. It is distinguished by the abundance of advanced hospitals and internationally recognized doctors. It has an advanced medical network in governmental, private, and military sectors. The importance of the study lies in demonstrating the role of marketing as an important factor for the promotion of medical tourism, which is reflected on the economical return of the state and represents one of the important axes of the growth of the Jordanian economy since they are considered centers of treatment and healthcare in the world. The study concluded that the information related to medical tourism that are used in marketing Jordan abroad are neither sufficiently clear nor direct, also the information of marketing medical tourism aboard does not demonstrate these products precisely. The study recommended the followings: following modern technological ways in marketing Jordan abroad from touristic perspective, clarifying the prices of provided touristic services to the tourist so as to grasp that there is a competitive advantage in comparison with other countries that provide same services. Keywords: Medical, Tourism, Marketing JEL Classifications: Z32, L83, M31